(untitled) (Journal of Universal Science Research, 2025)
The primary objective of this research is to analyze the influence of various stress-inducing factors on the onset and early progression of arterial hypertension among university students. This investigation focuses on identifying the interrelation between psychological stress, lifestyle deviations, and functional disturbances in cardiovascular regulation during a formative stage of adulthood.